Physical activity and depression of Chinese college students: chain mediating role of rumination and anxiety - Liu, Yanying; Feng, Qingkun; Guo, Kelei (Frontiers in Psychology, 2023)
Objective: To explore the relationship between physical activity and depression among college students, as well as the mediating role of rumination and anxiety. Methods: A total of 1292 Chinese college students were investigated by physical activity questionnaire, rumination scale, self-rating anxiety scale (SAS), and depression scale. Results: (1) There was a significant negative correlation between physical activity and depression (r = -0.399, p < 0.01), and the direct path of physical activity on depression was significant (β = -0.399, t = -13.374, p < 0.01). (2) Physical activity negatively predicted rumination (β = -0.322, t = -10.440, p < 0.01) and anxiety (β = -0.222, t = -7.089, p < 0.01). Rumination positively predicted anxiety (β = 0.283, t = 9.017, p < 0.01) and depression (β = 0.267, t = 9.046, p < 0.01). Anxiety positively predicted depression (β = 0.262, t = 8.902, p < 0.01). (3) Rumination and anxiety play a significant mediating role between physical activity and depression. The mediating effect involves three paths: physical activity→rumination→depression (the mediating effect value: -0.076); physical activity→anxiety→depression (the mediating effect value: -0.052). Physical activity→rumination→anxiety→depression (the mediating effect value: -0.021).